FRI0430 IXEKIZUMAB IMPROVES THE SIGNS AND SYMPTOMS OF PSORIATIC ARTHRITIS REGARDLESS OF SEX, DURATION OF DISEASE, OR BODY MASS INDEX IN TWO RANDOMIZED, PHASE 3 CLINICAL TRIALS. (June 2019) - Eder, Lihi; Odhav, Satish; Korkosz, Mariusz; Sprabery, Aubrey Trevelin; Gellett, Amanda M.; Lin, Chen-Yen; Park, So Young; Bertram, Clinton C.; Ogdie, Alexis
Abstract : Background: Ixekizumab (IXE) is a high-affinity monoclonal antibody that selectively targets interleukin-17A. During 24 weeks (wks) of treatment, IXE resulted in significantly greater improvements versus placebo (PBO) in the signs and symptoms of active psoriatic arthritis (PsA) in two randomized Phase 3 studies. 1, 2 Objectives: To evaluate the consistency of clinical response with IXE in demographic subsets of patients (pts) with active PsA. Methods: Clinical response to IXE was analyzed from an integrated database of 2 randomized, double-blind, Phase 3 studies in biologic Disease Modifying Anti-Rheumatic Drug (bDMARD)-naïve (SPIRIT-P1) pts or in pts with prior inadequate response or intolerance to TNF inhibitors (SPIRIT-P2). Analyses were conducted on subgroups defined by sex, body mass index (BMI), and duration of disease (<5 or ≥5 years) at baseline for pts who were randomly assigned to either PBO or the approved dosing regimen of IXE (80 mg IXE every 4 wks [IXE Q4W] with a starting dose of 160-mg IXE). Efficacy in each subgroup was evaluated as the percentage of pts at Wk 24 achieving ≥20%, 50%, or 70% improvement from baseline in the American College of Rheumatology criteria (ACR20/50/70) or minimal disease activity. Missing data were imputed using nonresponder imputation (NRI). Results: Response rates at Wk 24 (Table) were significantly (p<0.05) greater in pts receiving IXE versus PBO across all endpoints assessed in subgroups defined by sex, disease duration, and in pts with overweight and obese BMI at baseline. Response rates were significantly greater with IXE compared to PBO for ACR20 and ACR50 in the normal BMI subgroup and for ACR50 in the extreme obese BMI subgroup. Assessment of superiority of IXE versus PBO in underweight and extreme obese subgroups was limited by small sample sizes; only three patients (all receiving IXE Q4W) had underweight BMI at baseline. For all endpoints assessed, numerically greater response rates were observed with IXE Q4W in male versus female pts. Conclusion: IXE was superior to PBO in the treatment of pts with active PsA at Wk 24 regardless of sex or disease duration, as well as in normal, overweight, and obese BMI subgroups. References: [1] Mease, et al. Ann Rheum Dis. 2017 [2] Nash, et al. Lancet. 2017 Disclosure of Interests: Lihi Eder Grant/research support from: AbbVie, Eli Lilly and Company, Amgen, Celgene, UCB, Janssen, Novartis, and Pfizer, Consultant for: AbbVie, Eli Lilly and Company, Amgen, Celgene, UCB, Janssen, Novartis, and Pfizer, Satish Odhav Grant/research support from: AbbVie, Ardea Biosciences, AstraZeneca, BMS, Celgene Corporation, Centocor, Eli Lilly and Company, Galapagos, Genentech, GSK, Human Genome Sciences, Janssen, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer, Roche, Sanofi-Aventis, Takeda Pharmaceuticals, UCB, and Vertex Pharmaceuticals, Consultant for: AbbVie, Ardea Biosciences, AstraZeneca, BMS, Celgene Corporation, Centocor, Eli Lilly and Company, Galapagos, Genentech, GSK, Human Genome Sciences, Janssen, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer, Roche, Sanofi-Aventis, Takeda Pharmaceuticals, UCB, and Vertex Pharmaceuticals, Speakers bureau: AbbVie, Ardea Biosciences, AstraZeneca, BMS, Celgene Corporation, Centocor, Eli Lilly and Company, Galapagos, Genentech, GSK, Human Genome Sciences, Janssen, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer, Roche, Sanofi-Aventis, Takeda Pharmaceuticals, UCB, and Vertex Pharmaceuticals, Mariusz Korkosz Consultant for: Eli Lilly and Company, Novartis, Roche, MSD, UCB, and AbbVie, Speakers bureau: Eli Lilly and Company, Novartis, Roche, MSD, UCB, and AbbVie, Aubrey Trevelin Sprabery Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Amanda M. Gellett Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Chen-Yen Lin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, So Young Park Employee of: Eli Lilly and Company, Clinton C Bertram Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda